1989
DOI: 10.1002/ijc.2910430528
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of dihydropyrimidine dehydrogenase, thymidine phosphorylase and thymidine kinase activities in strongly and weakly malignant cultured murine neuroblastoma cells

Abstract: The C-1300 neuroblastoma tumor which arises spontaneously in the A/J mouse has been maintained in this mouse strain. Two different cell populations have been recognized in cultured C-1300 mouse neuroblastoma (MNB): (1) round, "neuroblast-like" cells, growing in suspension (poorly attached), that have a highly malignant behavior when injected into the A/J mouse (T1 cells); and (2) flat, "epithelioid" cells that attach well to surfaces and show low malignancy towards the inoculated animals (T2 cells). The specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…PD-ECGF/TP expression in NB tumor samples has not been reported. Williams et al have shown that PD-ECGF/TP enzymatic activity is much higher in weakly malignant than in strongly malignant murine NB cells (Williams and Tuchman 1989). Recent studies have indicated that PD-ECGF/TP expression in some cancers may be an independent prognostic factor rather than an index for angiogenesis (Yamamoto et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PD-ECGF/TP expression in NB tumor samples has not been reported. Williams et al have shown that PD-ECGF/TP enzymatic activity is much higher in weakly malignant than in strongly malignant murine NB cells (Williams and Tuchman 1989). Recent studies have indicated that PD-ECGF/TP expression in some cancers may be an independent prognostic factor rather than an index for angiogenesis (Yamamoto et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Queener et al 31) demonstrated that DPD activity in rat hepatomas decreased in parallel with the increase in tumor growth rate. In contrast, Williams and Tuchman 32) reported that DPD activity in mouse neuroblastoma cells increased during culture, whereas thymidine kinase activity decreased markedly.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Queener et al 31) demonstrated that DPD activity in rat hepatomas decreased in parallel with the increase in tumor growth rate. In contrast, Williams and Tuchman 32) reported that DPD activity in mouse neuroblastoma cells increased during culture, whereas thymidine kinase activity decreased markedly. Takechi et al 33) observed time-dependent increases in DPD activity during the growth of human fibrosarcoma HT-1080 cells and human pancreatic carcinoma MIAPaCa-2 cells in cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme can also act at a reversal direction -conversion of dTdR to thymine. High activity of TP was found in tumour cells [15]. To test if the enzyme is involved in a substrate cycle, the substrate kinetics was determined as follows.…”
Section: Determination Of the Substrate Kinetics Of Enzymesmentioning
confidence: 99%
“…To obtain cytoplasmic fraction, lysates were prepared as earlier described [14]. The supernatant was immediately used for activity assay of TK1 [14] and TS [15,16], respectively. B) Determination of dTdR substrate kinetics of TK1.…”
Section: Determination Of the Substrate Kinetics Of Enzymesmentioning
confidence: 99%